Temporal and Spatial Analysis of Trace Metal Ecotoxicity in Sediments of Chaohu Lake, China - Wenguang Luo; Zongjun Li; Ran Yi; Lijuan Han; Senlin Zhu (Toxics)
The species sensitivity distribution (SSD) analysis for aquatic ecosystems has been increasingly used in risk assessment. However, existing analyses of the impact of trace metals in lake sediments on aquatic organisms often neglect the spatiotemporal variability of trace metal release. This oversight can result in ecological risk assessments that lack specificity. To address this gap, we collected 32 core sediment samples from Lake Chaohu to systematically investigate the ecological toxicological risks posed by the release of eight trace metal indicators into the overlying water column under four hydrological scenarios throughout the year. Results indicated that only Cu, Pb, and Zn exhibit persistent toxicological risks. The comprehensive ecological toxicological risk of sediment trace metals showed spatial differences, increasing from the western region to the eastern region, i.e., western region < central region < eastern region. Seasonally, the risk levels are ordered as follows: May < September < November to April of the following year < June to August. The eastern region in summer (June to August) was identified as the high-risk area and period for trace metal pollution in sediments. Based on these conclusions, it is recommended to implement pollution control and environmental monitoring measures in the eastern region during the summer to effectively control the pollution and ecological risks of trace metals.